Keterkaitan Job Specification Pada Kinerja Karyawan - Aura, Raissa Rahma; Fitri, Nadia Khalishah; Yusuf, Muhammad Fachri; Ahmad, Aditya Fathi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the relationship between job specifications and employee performance in various company industries. Job specifications include the abilities, insight and experience needed by a company to achieve certain goals. Employee performance is measured based on several indicators such as production ability or productivity, work quality and employee efficiency. The research method used is the literature analysis method, where the researcher found that the appropriate work specification is to provide clear direction and teachings related to work. Therefore, these findings are discussed to help companies design job specifications that are in line with company goals in order to improve employee performance in order to help a company effectively achieve its goals.